ЗАСТОСУВАННЯ ГЕОМЕТРИЧНОГО ПІДХОДУ ДЛЯ ТРИФАЗНОГО СИЛОВОГО АКТИВНОГО ФІЛЬТРА - Жуйков , В.Я.; Миколаєць, Д.А. (Інститут електродинаміки НАН України, Київ, 2018)
The geometric approach with the use of the transition matrix from independent variables in a three-coordinate space to a dependent system with two independent variables is considered in this paper. A relationship that allows to express output variables through inputs are got. The space of vectors of input and output variables is constructed. References 9, table 1, figures 3.